Riba Dan Bunga Bank Dalam Perspektif Fikih Kontemporer - Noor Mutia Husna; Zulfa Rahmaniah (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Riba is one of the fundamental concepts in fiqh muamalah that is strictly prohibited in Islam. In modern economic practices, bank interest is often equated with riba, which has led to prolonged debates among scholars and economic practitioners. This article aims to analyze the concept of riba and bank interest from the perspective of contemporary Islamic jurisprudence by examining their definitions, legal foundations, types of riba, and scholarly views on bank interest practices. The research method employed is a literature study using a descriptive-analytical approach toward classical and contemporary fiqh sources. The findings indicate that the majority of contemporary scholars consider bank interest to be equivalent to prohibited riba, while a small number of scholars offer differing views under specific conditions and contexts. Therefore, the existence of Islamic financial institutions serves as an alternative solution to avoid riba-based practices within the modern banking system. Keywords: riba, bank interest, contemporary fiqh, Islamic economics. Abstrak Riba merupakan salah satu konsep fundamental dalam fikih muamalah yang secara tegas dilarang dalam Islam. Dalam praktik ekonomi modern, keberadaan bunga bank sering kali dipersamakan dengan riba sehingga menimbulkan perdebatan panjang di kalangan ulama dan praktisi ekonomi. Artikel ini bertujuan untuk menganalisis konsep riba dan bunga bank dalam perspektif fikih kontemporer dengan menelaah pengertian, dasar hukum, jenis-jenis riba, serta pandangan ulama terhadap praktik bunga bank. Metode penulisan yang digunakan adalah studi kepustakaan dengan pendekatan deskriptif-analitis terhadap sumber-sumber fikih klasik dan kontemporer. Hasil kajian menunjukkan bahwa mayoritas ulama kontemporer menyamakan bunga bank dengan riba yang diharamkan, sementara sebagian kecil lainnya memberikan pandangan berbeda dengan syarat dan konteks tertentu. Oleh karena itu, kehadiran lembaga keuangan syariah menjadi solusi alternatif untuk menghindari praktik riba dalam sistem perbankan modern. Kata Kunci: riba, bunga bank, fikih kontemporer, ekonomi syariah